2021
DOI: 10.1002/cac2.12126
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in refractory diffuse large B‐cell lymphoma: results from a multicenter real‐world study in China

Abstract: Background Diffuse large B‐cell lymphoma (DLBCL) patients refractory to rituximab‐based immunochemotherapy have a dismal prognosis. However, the definition of refractory DLBCL remains inconsistent and no large cohort study data is available from Asian countries. To validate the definition and outcomes of refractory DLBCL in China, we conducted a multicenter, retrospective cohort study. Methods The REtrospective AnaLysis of Treatment REspoNse of refractory DLBCL (REAL‐TREND) study was performed using real‐world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…These combination results are consistent with a significant anti-DLBCL contribution of selinexor to standard chemotherapy and are being further evaluated. Single-agent oral selinexor treatment was associated with a longer OS than expected based on contemporary case series [10][11][12] despite patient treatment, response history, age, and comorbidities. Given the beneficial impact of selinexor as a single agent and the poor prognosis of many patients, randomized studies of selinexor in combination with a variety of other anti-DLBCL agents are planned.…”
Section: To the Editormentioning
confidence: 79%
See 1 more Smart Citation
“…These combination results are consistent with a significant anti-DLBCL contribution of selinexor to standard chemotherapy and are being further evaluated. Single-agent oral selinexor treatment was associated with a longer OS than expected based on contemporary case series [10][11][12] despite patient treatment, response history, age, and comorbidities. Given the beneficial impact of selinexor as a single agent and the poor prognosis of many patients, randomized studies of selinexor in combination with a variety of other anti-DLBCL agents are planned.…”
Section: To the Editormentioning
confidence: 79%
“…10 Cleveland Clinic, Cleveland, USA. 11 APHP, Hemato-oncology, Saint-Louis Hospital, Paris, France. 12…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Ibrutinib plus buparlisib (a pan-PI3K inhibitor) for 37 patients with R/R DLBCL achieved an ORR of 31% ( 21 ). In the REAL-TREND study ( 22 ), a real-world retrospective analysis of treatment response of R/R DLBCL from 8 centers in China (including our center), the pooled ORR of salvage chemotherapy was 30% and the CRR was 9%. Our results with high efficacy indicated that zanubrutinib may act synergistically with conventional chemotherapeutic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, antibody-based therapy could eliminate all tumor cells; however, it is reported that 4-12% of patients who received the rituximab-based therapy experienced primarily refractory and 17-40% relapse after complete remission (CR) or partial remission (PR). Moreover, 12-60% of these patients experience tumor recurrence after the second-or third-line therapy [2][3][4]27]. The resistance mechanisms of rituximab remain elusive, which might be associated with tumor microenvironment (TME), host immunologic factors, pharmacokinetics, downregulation or loss of CD20 [26,28].…”
Section: Discussionmentioning
confidence: 99%